Developing of annual program guidance and counseling in higher education - Kurniawan, Fandy (COUNS-EDU: The International Journal of Counseling and Education, 2018)
This study aims to develop and determine the feasibility of the annual program of guidance and counseling in higher education. The method used in this research is Research and Development (R & D) Research and development carried out by adopting the concept of research and development by Borg and Gall. Based on product test using inter-rater agreement models, it is concluded that the product has fulfilled the content validity of 0.76 or can be categorized as valid (good). Furthermore, based on the results of Focus Group Discussion (FGD), it is concluded that the product can be categorized well, but needs to be refined by making improvements given.